"Nature Cannot Be Fooled": A Dual-Equilibrium Simulation of Climate Change. (December 2021) - Sunny, Sanwar A.
Although organizational scholars and social scientists have recently called for the integration of the natural environment into management theories, natural scientists have long espoused integrative frameworks. Gottfried Leibniz, the founder of differential calculus, sought integration long before the industrial revolution and Ludwig Boltzmann, the pioneer of statistical mechanics, before the oil boom. Alfred Lotka formalized this notion long before the financial crisis of 1933, while Howard Odum extended it before the oil crisis of 1973. In this essay, and accompanying simulation, I summarize and visualize how the laws of thermodynamics are independently insufficient yet jointly necessary alongside market economics to address the pressing problem of global climate change.